PENERAPAN PROGRAM SISTEM KREDIT SEMESTER (SKS) PENDIDIKAN AGAMA ISLAM DI SMA MUHAMMADIYAH 3 JAKARTA - Wahid, Abdurrahman (Jurnal Pendidikan Islam, 2016)
This research aims to reveal the depth understanding   of the application of the System Credit Semester (SKS)  of Islamic religious education in SMA Muhammadiyah 3. This research  used a qualitative descriptive method using Ethnographic approach. These results indicate that there are values in the moral education. The results of this study indicate that SMA Muhammadiyah 3 need to review the application of credits that will be applied in the teaching syllabus of Religious Education/Akhlaq for students.